Employed My Own Strategy: Exploring Primary Headteachers Organisational and Professional Socialisation - Mohd Tahir, Lokman; Mustamaal@Jamal, Aede Hatib; Mohd Yusof, Sanitah; Ali, Mohd Fadzli; Hassan, Zainudin; Abd Hamid, Mohd Zolkifli (Universiti Utara Malaysia Press, 2018)
Purpose - The main purpose of this study was to explore primary headteachers perceptions of their professional and organisational socialisation within their novice years as school leaders. There is a lack of studies exploring primary headteachers socialisation within the Malaysian primary education context.